Enhancing Agricultural Water Efficiency through Conservation and Groundwater Management in Akola District, Vidarbha Region - , R. S. Patode; , Anita Chorey; , Ranee Wankhade; , M. M. Ganvir; , V. P. Pandagale; , R. S. Mali; , Sachin Morey; , Pawan Fukat; , M. Sinha (Archives of Current Research International, 2025)
Rainfall is the single input in the Dryland agriculture for fulfilling the crop water requirement. Based on the watershed approach it is possible to make a quantitative evaluation of water resources and their change under the influence of man's activities. Knowledge of the water availability assists the prediction of the consequences of artificial changes in the regime of streams, lakes, and ground-water basins. An understanding of the water balance is also extremely important for providing protective irrigations. To explore the impact of water conservation configurations on groundwater establishment at Kajaleshwar micro watershed of Tq. Barshitakli, Distt. Akola in Vidarbha region of Maharashtra the study was completed under Agri- Consortia Research Platform on Water, All India Coordinated Research Project for Dryland Agriculture, Dr. Panjabrao Deshmukh Krishi Vidyapeeth, Akola. Drainage (Nala), widening and deepening and repairs of established rainwater harvesting and storage structures were ensured for impact evaluation. Groundwater data was collected for 51 observation wells in the vicinity of 10 cement nala bunds (CNBs) for analysis of rainwater harvesting influence on groundwater regime in micro watershed area. During 2017 (36 wells) average depth of water level was 4.07 m and during 2019 (36+15= 51wells) it was increased and found to be 2.81m. Well water levels were observed to be increased in 2019 as compared to 2017. The yield of soybean crop with one protective irrigation at pod filling stage during Kharif season was (1483 kg/ha) increased by 26 % as compared to without irrigation (1180 kg/ha). During Rabi season on an average the yield of Chickpea crop with two protective irrigations at initial and pod filling stage was (1773 kg/ha) increased by 38.73% as compared to without irrigation (1278 kg/ha). In the event of a protective irrigation, the yield of Chickpea was (1539kg/ha) increased by 20.42 % as compared to without irrigation (1278 kg/ha). Thus, it can be inferred that if conservation measures are implemented technically then yield sustainability in agriculture can be achieved. Due to acceptance of comparable types of rainwater harvesting and non-natural recharge structures, groundwater possessions will be augmented. This will support in expansion of integrated farming systems which eventually will be helpful in increasing the yields and water efficiency of the area where such works are being accepted.